Empowerment ability of main caregivers of children with intracranial tumors after surgery: a cross-sectional survey - Zhou, Wen; Yang, Wen; Cao, Tian (Frontiers in Pediatrics, 2025)
BackgroundThe empowerment capacity of caregivers exerts a significant impact on children's prognosis. This study aims to analyze the empowerment ability of primary caregivers of children who have undergone craniotomy, thereby providing evidence-based support for pediatric nursing practice.MethodsParticipants in this study included main caregivers of children with intracranial tumors who underwent surgical treatment in our hospital between February 2022 and April 2025. The empowerment ability of these main caregivers was assessed using the Main Caregivers’ Empowerment Measurement (MCEM) scale. Correlation analysis and multiple linear stepwise regression analysis were performed to identify potential influencing factors.ResultsA total of 242 main caregivers were enrolled in this study. The average empowerment score among these caregivers was 160.64 ± 15.07. The “Personal Resources” and “Care Knowledge and Skills” dimensions yield the lowest scores across all dimensions. Correlation analysis demonstrated that the child's age (r = 0.581), place of residence (r = 0.546), caregiver's gender (r = 0.604), caregiver's age (r = 0.626), educational level (r = 0.615), and monthly per capita income (r = 0.586) were all significantly associated with the empowerment ability (all p < 0.05). Furthermore, multivariate linear regression analysis identified those factors as significant influencing factors of caregiver empowerment. These selected variables accounted for 58.8% of the variance in caregivers’empowerment ability.ConclusionGiven the substantial room for improvement in the empowerment levels of main caregivers, targeted strategies are urgently needed to address this gap. Healthcare professionals should therefore design interventions that are tailored to the identified influencing factors to enhance caregivers’ empowerment capacities.